Akulturasi Budaya Hibrid pada Pagelaran Musik Jazz Gunung sebagai Identitas Global dalam Meningkatkan Potensi Wisata - Mochammad Djauhari; Jokhanan Kristiyono (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2020)
AbstractThis study analyzes the process of acculturation of hybrid culture in the performing arts of Mount Bromo Jazz with the local culture of the Tengger tribe. The acculturation of hybrid culture as a global identity in increasing local tourism potential is the culture of the Tengger tribe, Bromo. By using a discourse analysis research methodology, researchers analyze and describe the dialectics to the discourse that occurs in the process of acculturation of hybrid culture at the Bromo mountain jazz performance. The development of Jazz music spread throughout the world, including in Indonesia. Jazz music is quite popular and is loved by many people, especially young people. At present, there are enough jazz shows that are often held in Indonesia. It is interesting to study and analyze that in this Bromo Jazz music performance the concept of performance and music is a combination of local culture and western culture. Performances by local Indonesian musicians together with global musicians around the world. Some new music works were created through a collaborative process between local musicians and foreign (global) musicians. The results of this study are the local culture of the Tengger tribe with global culture, namely the performance of jazz music into the potential of hybrid culture acculturation in the Sukapura Probolinggo East Java region. This study also illustrates how the process of creating a hybrid culture in Bromo Jazz music performance. The conclusions obtained from this study are the development of the hybrid music culture of Mount Bromo Jass as a potential world-class tourist destination.Keywords: Hybrid Culture, Bromo Mountain Jazz, Acculturation, IdentityAbstraksiPenelitian ini menganalisa proses akulturasi budaya hibrid pada seni pertunjukan Jazz Gunung Bromo dengan budaya lokal suku Tengger. Akulturasi budaya hybrid sebagai identitas global dalam meningkatkan potensi wisata lokal yaitu budaya suku Tengger, Bromo. Dengan menggunakan metodologi penelitian analisa wacana, peneliti menganalisa dan mendeskripsikan dialektika hingga diskursus yang terjadi dalam proses akulturasi budaya hybrid pada pagelaran musik jazz gunung Bromo. Perkembangan musik Jazz menjalar ke seluruh dunia, termasuk di Indonesia. Musik jazz tergolong musik yang cukup populer dan disenangi oleh banyak kalangan, terutama anak muda. Menarik dikaji dan dianalisa bahwa pada pagelaran musik Jazz Gunung Bromo ini konsep pertunjukan dan karya musiknya merupakan gabungan antara budaya lokal dan budaya barat. Pertunjukan para musisi lokal Indonesia bersama dengan para musisi global dunia. Beberapa karya musik baru diciptakan dengan proses kolaborasi bersama antara musisi lokal dengan musisi luar (global). Hasil dari penelitian ini adalah Budaya lokal suku Tengger dengan budaya global yaitu seni pertunjukan musik jazz menjadi potensi akulturasi budaya hybrid di kawasan Sukapura Probolinggo Jawa Timur. Penelitian ini juga menggambarkan bagaimana proses terciptanya budaya hybrid pada pagelaran music Jazz Gunung Bromo. Simpulan yang didapat dari penelitian ini adalah pengembangan budaya hybrid musik Jazz Gunung Bromo sebagai potensi destinasi wisata berkelas duniaKata Kunci: Hibrid, Jazz Gunung Bromo, Akulturasi, Identitas